Enhancing Human Capital Development Among Non-Lecturer Educational Staff: Challenges and Leadership Solutions - Andriani, Idaya; Hamengkubuwono; Istan, Muhammad (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2024)
This study investigates the challenges faced by non-lecturer educational staff in developing human capital and explores leadership solutions within a higher education institution in Bengkulu province. Employing a qualitative descriptive methodology, data were collected through interviews, observations, and open-ended questionnaires from 20 staff members and two leaders. Key findings reveal difficulties in balancing education and work, limited access to relevant training, and obstacles in skill development. Leadership responses include flexible educational schedules, improved technology infrastructure, and enhanced cross-unit collaboration. The study highlights the need for comprehensive solutions to improve service quality, innovation, and institutional adaptation. Limitations include the study's focus on a single university and reliance on qualitative data. Further research should explore these dynamics across diverse educational contexts and assess the long-term impacts of proposed solutions.